13 Mei 1969 di Kuala Lumpur - Abdul Rahman Ibrahim (Dewan Bahasa dan Pustaka, 2018)
Racial riots between Malays and Chinese on May 13, 1969 in Kuala Lumpur, Malaysia as a result of political, social, and economic instability